Severe COVID-19: NLRP3 Inflammasome Dysregulated - van den Berg, Daan F.; te Velde, Anje A. (Frontiers in Immunology, 2020)
SARS-CoV-2 might directly activate NLRP3 inflammasome resulting in an endogenous adjuvant activity necessary to mount a proper adaptive immune response against the virus. Heterogeneous response of COVID-19 patients could be attributed to differences in not being able to properly downregulate NLRP3 inflammasome activation. This relates to the fitness of the immune system of the individual challenged by the virus. Patients with a reduced immune fitness can demonstrate a dysregulated NLRP3 inflammasome activity resulting in severe COVID-19 with tissue damage and a cytokine storm. We sketch the outlines of five possible scenarios for COVID-19 in medical practice and provide potential treatment options targeting dysregulated endogenous adjuvant activity in severe COVID-19 patients.